Penerapan Metode Design Thinking dalam Perancangan UI/UX Aplikasi Pendakian Gunung Berbasis Mobile di Jawa Timur - Putra, Rio Alghaniy; Najaf, Abdul Rezha Efrat; Mukhlis, Iqbal Ramadhani (Universitas Multi Data Palembang, 2026)
The increasing interest of the people of East Java in mountain hiking activities has created a need for digital solutions that can integrate information, preparation, and hiking safety. This study aims to design the user interface and user experience of a mobile-based mountain hiking application called Mountzy using the Design Thinking method. The stages applied include empathize, define, ideate, prototype, and test, with a focus on the needs of hikers in East Java. The design results are realized in the form of information architecture, wireframes, and high-fidelity prototypes that include key features such as Pantau Langit, Hiking Planning, Sewa Aja (equipment rental), and Community Forum. Usability testing was conducted using Maze and the System Usability Scale (SUS). The results show a Maze score of 83 and an average SUS score of 83.20, which fall into the excellent and acceptable categories. These results indicate that the Mountzy application has good usability and is feasible for further development.